Evaluation of Physics‐Based Data Assimilation System Driven by Neutral Density Data From a Single Satellite - Dexin Ren; Jiuhou Lei (Space Weather)
Abstract Accurate forecast of the thermospheric density is critical to the space community. The data assimilation approach that is based on the self‐consistent upper‐atmosphere model may provide better predictive capability of the coupled thermosphere system. In this study, a physics‐based assimilation system (hereafter referred to as PIDA) that is based on the Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model was used to validate the capability of reproducing the evolution of the global thermosphere state. The effective solar and geophysical drivers were estimated by ingesting neutral density from a single satellite into the PIDA. It was found that the PIDA can reproduce the temporal variation of the global thermospheric density at around the altitude where the orbit density was ingested. Furthermore, the PIDA is also capable of capturing the temporal evolution of the thermospheric density at various altitudes. However, a systematic bias, depending on altitude, is seen in the modeled neutral density of the PIDA. Moreover, this systematic bias in the thermospheric density is likely ascribed to the overestimation of the density in the lower thermosphere. Consequently, the spatial and temporal evolutions of the lower thermosphere under various conditions should be considered carefully in the physics‐based data assimilation system. Additionally, the assessments of the obtained results suggested that the observations of multiple parameters at different altitudes are required to be assimilated into the thermospheric model.